The definition of "Insider" in section 3 of the securities markets Act 1988: A review and comparison with other jurisdictions - Su, Z.; Berkahn, M. A. (My University, 2003)
Statutory definitions of what constitutes an “insider” for the purposes of insider trading laws may be based on either a “person connection” approach or an “information connection” approach. The “person connection” approach defines “insider” by reference to the relationship of the person to the public issuer of securities, while the “information connection” approach considers anyone who has material price-sensitive information about the issuer to be an insider, regardless of his or her relationship to the issuer. In common with Japan, Hong Kong and China, New Zealand’s insider trading law — the Securities Markets Act 1988 — uses a person connection approach in its definition of “insider”. Other jurisdictions, however, including both the United Kingdom and Australia, have, to varying degrees, recently amended their definitions to reflect the information connection approach. The United States, although the first country to address the issue of insider trading, lacks a statutory definition of “insider” and instead relies on generally applicable laws against securities fraud. It has developed a definition with elements of both approaches. This paper reviews the definitions in use in the United States and in other countries (including New Zealand) which have been influenced by the American experience. It concludes that the narrow, relationship-based approach does not capture some conduct that may be damaging to the integrity of the securities market. A definition based on the information connection approach (perhaps combined with elements of the person connection approach) may therefore be preferable to New Zealand’s current definition.
Keywords: Insider trading; Insider trading laws; Securities trading